Immunohistochemical Markers for Schwannomas, Neurofibromas and Malignant Peripheral Nerve Sheath Tumors—What Can the Recent Literature Tell Us? - Guedes-Corrêa, José Fernando; Cardoso, Rodrigo Salvador V. (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
Introduction Schwannomas and neurofibromas are the two most common benign neoplasms of the peripheral nerve sheath, and although they are generally easy to distinguish, in some cases, they can closely resemble one another. Furthermore, malignant peripheral nerve sheath tumors (MPNSTs), another example of peripheral nerve sheath neoplasm, may likewise constitute, due to their morphology and lack of specific immunohistochemical markers, a challenging diagnostic.Objective To bring attention to new and promising biomarkers for schwannomas, neurofibromas and MPNSTs and to outline, based on the recent literature, a immunohistochemical profile for each neoplasm at hand, as well as to emphasize the need for further studies that could help us understand their diagnostic potential and disrupt our dependence of limited and nonspecific biomarkers.Methods An overview of the recent literature published in English on both the classical promising immunohistochemical markers of schwannomas, neurofibromas and MPNSTs was performed. We discarded case reports.Conclusions There is still a lack of specific biomarkers for peripheral nerve tumors. However, plenty of new immunohistochemical markers have been coming to light with presumed higher specificity and more diverse helpful uses than the classical ones. For example, Sox10 is a good biomarker for differentiating schwannomas and neurofibromas from sarcomas, calretinin schwannomas from neurofibromas, TLE1 and HMGA2 MPNSTs from sarcomas, and nestin, EGFR, p16 and Ki-67 MPNSTs from different types of schwannomas and neurofibromas. There is still need for further studies; however, the potential of some of these promising markers, among others, should not be disregarded.
Keywords: immunohistochemistry; biomarker; nerve sheath neoplasm(s); schwannoma; neurofibroma; malignant peripheral nerve sheath tumor